Notice of Retraction Simulation of Feedforward-Feedback Control of Dissolved Oxygen of Microbial Repeated Fed-batch Culture - Ling Gao; Huibin Lin (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
Notice of Retraction-----------------------------------------------------------------------After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting ijeei.iaes@gmail.com.-----------------------------------------------------------------------Fed-batch culture is often used in industry, and dissolved oxygen (DO) concentration control is important in fermentation process control. DO control is often applied by using feedback (FB) control strategy. But, feedforward-feedback (FF-FB) control has the advantage in dealing with the time-varying characteristics resulted from the cell growth during the fermentation process. Mathematical modeling and computer simulation is a useful tool in analysis of the control system.  In this research, the FF-FB DO control and FB substrate control of repeated fed-batch culture process is modeled and simulated. The results showed the feasibility of the control strategy. These results are useful for control system development and process analyses and optimization.